Analisis kecekapan teknik dalam industri skel kecil dan sederhana di Malaysia - Mohd Noor, Zulridah; Ismail, Rahmah (Universiti Utara Malaysia, 2007)
The Small and Medium Scale industries (SMIs) comprise more than 90% of the total number of enterprises in the manufacturing sector in Malaysia. Therefore, SMIs play a major role especially in generating employment opportunities. Technical efficiency of SMIs has a significant influence on overall technical efficiency of the manufacturing sector. Firms in SMIs are generally found to exhibit relatively low levels of technical efficiency as compared to the Large Scale Industries (LSIs) and this influence their contributions to the gross domestic product and national competitiveness. This article aims to analyse technical efficiency of 95 firms in SMIs in Malaysia using survey data conducted in 1997. The analysis uses two stage procedures. In the first stage, technical efficiency is calculated for every firm using non-parametric frontier methodology known as Data Envelopment Analysis (DEA). In this analysis, we adopt an input oriented approach at constant return to scale and variable return to scale technology. In the second stage, censored regression analysis using a Tobit model is estimated to identify the determinants of technical efficiency, that were computed in the first stage. The study found that most firms in SMIs are technically inefficient and operate at an increasing return to scale. Firm size and level of machinery utilisation have a positive significant effect on technical efficiency.